PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK PERUSAHAAN SUB SEKTOR KOSMETIK DAN RUMAH TANGGA TAHUN 2015 – 2019 - Allen Samuel L. Rajagukguk; Alfred Doloksaribu (Program Studi Magister Manajemen Universitas Advent Indonesia, 2021)
Every individual or company or business entity is obliged to contribute in the form of taxes to the state aimed at the welfare of the community and the state. In particular, the tax company or business entity is a burden that reduces profits. Therefore, the purpose of this study is to determine the effect of profitability and leverage on tax aggressiveness. The data sources for this research are financial reports from six cosmetic and household sub-sector companies from 2015 to 2019, using purposive sampling. The number of samples used as many as 30 samples. Based on the results of statistical tests, there is a negative influence between profitability and tax aggressiveness. However, for leverage there is no effect on tax aggressiveness. Likewise, there is no effect simultaneously between profitability and leverage on tax aggressiveness.